PENGARUH MOTIVASI BERWIRAUSAHA, PENDIDIKAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA (Studi Kasus pada Mahasiswa STIE Muhammadiyah Cilacap) - Yuni Rahmawati; Zamroni (JURNAL EKONOMI, 2020)
Abstract This study aims to test Entrepreneurship Motivation (X1), Entrepreneurship Education (X2) and Family Environment (X3) towards the students interest of Entrepreneurship in STIE Muhammadiyah Cilacap. The populations in this study is 184 students STIE Muhammadiyah Cilacap year 2016, 2017, 2018 and took sample of 65 respondent. The sampling technique used purposive sampling. Data collection technique used questionnare. Analysis prerequisite test included normality test, multicolinearity test and heteroscedasticity test. The data analysis technique used multiple linear regression analysis. The result of this study showed that : (1) there was positif and significant influence of Entrepeneurship Motivation towards the students interest of Entrepreneurship in STIE Muhammadiyah Cilacap with t value (2,797) greater than t table (1,999) and significant value less than 0,05 is 0,007. (2) there was positif and significant influence of Entrepeneurship Education towards the students interest of Entrepreneurship in STIE Muhammadiyah Cilacap with t value (2,036) greater than t table (1,999) and significant value less than 0,05 is 0,046. (3) there was positif and significant influence of Family enviroment towards the students interest of Entrepreneurship in STIE Muhammadiyah Cilacap with t value (3,509) greater than t table (1,999) and significant value less than 0,05 is 0,001. There was a positive and significant influence of Entrepreneurship Motivation, Entrepreneurship Education and Family Enviroment towards the students interest of Entrepreneurship in STIE Muhammadiyah Cilacap with F value (18,479) greater than F table (2,75) and significant value less than 0,05 is 0,000. Keywords : Entrepreneurship Motivation, Entrepreneurship Education, Family Enviroment, Interest Entrepeneurship